2019
DOI: 10.1093/sleep/zsz239
|View full text |Cite
|
Sign up to set email alerts
|

HLA and sleep parameter associations in post-H1N1 narcolepsy type 1 patients and first-degree relatives

Abstract: Study Objectives To explore HLA (human leukocyte antigen) in post-H1N1 narcolepsy type 1 patients (NT1), first-degree relatives and healthy controls, and assess HLA associations with clinical and sleep parameters in patients and first-degree relatives. Methods Ninety post-H1N1 NT1 patients and 202 of their first-degree relatives were HLA-genotyped (next generation sequencing) and phenotyped (semistructured interviews, Stanfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…These findings are in line with those of two recent reports describing these associations in small numbers of post-H1N1 NT1 patients that report positive associations of post-H1N1 with HLA-DQ7 and negative associations with HLA-DQ2 (Lind et al, 2019;Juvodden et al, 2019). Both these and other studies in NT1 patients before and after the H1N1 pandemic also describe the same associations that we found (Mignot et al, 2001;van der Heide et al, 2015;Hong et al, 2007;Tafti et al, 2014;Bomfim et al, 2017;Tafti et al, 2016;Han et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with those of two recent reports describing these associations in small numbers of post-H1N1 NT1 patients that report positive associations of post-H1N1 with HLA-DQ7 and negative associations with HLA-DQ2 (Lind et al, 2019;Juvodden et al, 2019). Both these and other studies in NT1 patients before and after the H1N1 pandemic also describe the same associations that we found (Mignot et al, 2001;van der Heide et al, 2015;Hong et al, 2007;Tafti et al, 2014;Bomfim et al, 2017;Tafti et al, 2016;Han et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Following these epidemiological and laboratory reports, a discussion on the existence of a post-H1N1 NT1 variant has arisen, with specifically Scandinavian countries making the distinction between sporadic and post-H1N1 NT1. Several recent Scandinavian studies report HLA-DQ-haplotypes associated specifically with post-H1N1 NT1 (HLA-DQ2, HLA-DQ7) (Juvodden et al, 2019;Lind et al, 2019). These reports started a discussion about whether different immunological mechanisms may be involved in post-H1N1 NT1.…”
Section: Introductionmentioning
confidence: 99%
“…It is also demonstrated that the other related respiratory viral infections, including influenza and MERS-CoV, lead to various responses in infected patients through epigenetic modulation (Menachery et al 2018 ). In addition, it is indicated that the HLA-C locus is linked to hypnagogic hallucinations and sleep paralysis in post-H1N1 narcolepsy type 1 individuals (NT1) (Juvodden et al 2020 ). Despite its long and close relationship with HLA-A and B, HLA-C expression on the cell surface is significantly lower than HLA-A and B (Apps et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In both instances, all cases are DQB1*06:02 positive and share the other major HLA risk factors. In addition, the only consistently associating non-HLA association in vaccination-related NT1 is TRA [ 36 , 39 ]. This association is most likely also the only one with large enough effect size to be detectable in the relatively small studies.…”
Section: Genetic Factors In Nt1 Provide Evidence For Immunitymentioning
confidence: 99%